Constructing Singapore public space - Hee, Limin (Springer, 2017)
This book presents possible alternatives and interpretations to the well established notion in the mostly western discourse on public space. The discourse on public space as understood in the democratic-rationalist tradition, when applied to the Singaporean public space, would offer much criticism but would not be adequate in identifying alternative processes that allow for transformative potentials in public space. Thus said, the objectives of this book are: 1. To develop a conceptual frame of reference to construct the discourse on Singapore public space 2. To form a preliminary model of Singapore public space through analyzing case studies 3. To understand the modes, methods of production and representation of these public spaces within the rapidly changing urban context 4. To situate these constructions of public space and its possible trajectories within the larger discourse on public space, and to examine the viability of such a construction and interpretive model of public space.
Keywords: Public spaces -- Singapore.; City planning -- Singapore.; Civic improvement -- Singapore -- Case studies.; Sociology, Urban -- Singapore.; Singapore.; elektronické knihy; electronic books